2014
DOI: 10.1177/1715163514535731
|View full text |Cite
|
Sign up to set email alerts
|

Patient attitudes regarding the role of the pharmacist and interest in expanded pharmacist services

Abstract: Background: Pharmacists are consistently ranked among the most trusted professionals, and research shows high levels of satisfaction with pharmacist services. Studies have also shown that the public is generally unaware of the full range of roles and responsibilities of a pharmacist. The purpose of this study was to explore the public's knowledge and attitudes regarding the role of the community pharmacist and to determine their likelihood of using expanded pharmacist services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 9 publications
4
68
0
Order By: Relevance
“…These findings are supported by previous Canadian research that can be interpreted to show that the public views pharmacists as health care professionals, just like doctors and nurses; as drug experts; and as a resource for information and advice about their health. [7][8][9] Respondent perceptions in this study revealed the importance of communicating well, ensuring ongoing confidentiality of information and providing quality information to patients regarding their medications. Previous research has highlighted the importance of pharmacist communication skills in influencing patient satisfaction levels and trust in their pharmacist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are supported by previous Canadian research that can be interpreted to show that the public views pharmacists as health care professionals, just like doctors and nurses; as drug experts; and as a resource for information and advice about their health. [7][8][9] Respondent perceptions in this study revealed the importance of communicating well, ensuring ongoing confidentiality of information and providing quality information to patients regarding their medications. Previous research has highlighted the importance of pharmacist communication skills in influencing patient satisfaction levels and trust in their pharmacist.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recent surveys of public perceptions of ESOP services in Canada have found mixed results, with limited support for granting pharmacists prescribing authority but greater support for ESOP services related to minor ailments and prescription refills. 7,8 Understanding public perceptions of the knowledge, skills and attitudes required by pharmacists to perform ESOP services will provide insight into public factors affecting the uptake of these new pharmacist roles. Recent Canadian polling results suggest that the public is supportive of ESOP services, 9 but gaps remain in our understanding about which perceptions are the most important influences on a patient's decision to use ESOP services.…”
Section: Original Researchmentioning
confidence: 99%
“…Pharmacists are the most accessible healthcare providers to the public, and they represent the front line professional element of health care who are focusing on the self‐care for the population . Community‐based pharmacy services have evolved greatly from the conventional drug dispensing methods . Drive‐thru or drive‐through pharmacy service is one example of the numerous newly emerging community pharmacy services, which was started in 1990 in the United States of America (USA) via Walgreens Pharmacies (the second‐largest pharmacy store chain in the United States) and now it is scattered across the USA.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Community-based pharmacy services have evolved greatly from the conventional drug dispensing methods. [1,4,5] Drive-thru or drivethrough pharmacy service is one example of the numerous newly emerging community pharmacy services, [6] which was started in 1990 in the United States of America (USA) via Walgreens Pharmacies (the second-largest pharmacy store chain in the United States) and now it is scattered across the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it is noteworthy that despite lack of support most of the pharmacists (i.e. 90%) adopted prescribing and moved out of the conventional ‘counting pill and dispensing’ role of pharmacists …”
Section: Discussionmentioning
confidence: 99%